Infrared Thermography to Assess Dermatomal Levels of Labor Epidural Analgesia With 1 mg/mL Ropivacaine Plus 0.5 mg/mL Sufentanil: A Prospective Cohort Study. Issue 4 (December 2020) - Bouvet, L.; Roukhomovsky, M.; Desgranges, F.P.; Allaouchiche, B.; Chassard, D.
Abstract : ( Int J Obstet Anesth . 2020;41:53–58) Epidural analgesia is considered the gold standard for labor analgesia. However, there are times when this technique fails to provide adequate analgesia and inadequate and/or failed epidural analgesia predicts failed conversion to anesthesia for cesarean delivery. The effectiveness of epidural analgesia can be determined early via verbal pain scores and testing the upper limit of the sensory block using cold sensation. Unfortunately, these methods are relatively subjective and can be unreliable. Thus, an objective tool for assessment of epidural spread of local anesthetic would be invaluable. This preliminary cohort study aimed to assess whether lumbar epidural analgesia brought forth significant change in cutaneous temperature (as measured by infrared thermography). In addition, the study also assessed whether the use of infrared thermography could aid in the prediction of failed epidural analgesia.